The Relationship between Perceived Life Changes and Mental Health in Family Caregivers of Patients with Heart Failure who Referred to Rajaei Cardiovascular Medical and Research Center, Tehran - Reza Negarandeh; Marjan Delkhosh; Elham Ghasemi (Shiraz University of Medical Sciences, 2015)
Abstract Background: Caring for a patient with heart failure can be a challenging and stressful situation. However, researchers have paid less attention to caregiving outcomes in heart failure caregivers. This study was conducted to investigate the relationship between perceived life changes and mental health of family caregivers of heart failure patients. Methods: Through a correlational design, a convenience sample of 90 Iranian family caregivers of patients with heart failure was selected. Data were collected using demographic-clinical characteristics form, Bakas Caregiving Outcomes Scale and General Health Questionnaire-28. Data were analyzed in SPSS using independent t-test, one-way ANOVA, Pearson correlation coefficients, and multiple regression analysis. Results: Half of the caregivers reported that their lives had changed for the worse and nearly three fourths were suspected cases of mental disorders. There was a strong negative correlation between perceived life changes and mental health (r=-0.607, P<0.001). This finding remained consistent (B=-0.522, P<0.001) even when potential confounding factors including caregiver's age (B=-0.222, P=0.016), caregiver's marital status (B=-6.085, P=0.025), and patient's age (B=-0.153, P=0.030) were controlled. Being younger, unmarried caregiver and caring of younger patients were identified as other correlated factors of poor caregivers 'mental health. Conclusion: The strong negative correlation between perceived life changes and mental health in caregivers of patients with heart failure suggests that the heart failure caregivers with poor mental health may benefit from nursing interventions that improve appropriate coping with life changes related to caregiving.